Factors Influencing Continuance Usage Intention of Mobile Health Services in New Normal Era in Indonesia - Fatima Shellya Shahab; Inge Susilo; Widiyanto Nugroho; Julbintor Kembaren (Cakrawala Repositori IMWI, 2023)
Mobile Healthcare Services has been present prior to the COVID-19 pandemic but were not widely utilized by customers and healthcare providers. However, the emergence of the pandemic and the subsequent implementation of quarantine and social distancing protocols catalyzed a shift towards remote services, with mobile healthcare services becoming the preferred option for customers and healthcare providers due to the safe access and delivery of services without the risk of contact with the virus. As outdoor mobility was limited and public places were restricted, internet and online services became the main options for people. With the widespread distribution of vaccines in most countries, the number of infections has decreased significantly, resulting in the revocation of quarantine and social distancing regulation, and a return to normal public activity. Research related to Mobile Healthcare Services in Indonesia is still limited, therefore there is still limited understanding regarding customers behavior intention in using the Mobile Healthcare Services post pandemic era. This study aims to understand consumer behavior intentional in the adoption of Mobile Health Services in the post-pandemic era by applying the Unified Theory of Acceptance and Use of Technology (UTAUT). An online survey was conducted by distributing online questionnaires via Google Form among 200 respondents in DKI Jakarta, Banten and West Java provinces who had previously used Mobile Healthcare Services. The results revealed that Performance Expectancy, Perceived Reliability, Perceived Usefulness, and Satisfaction had a significant influence on Behavioral Intention, while Effort Expectancy, Facilitating Condition, and Social Influence were not significantly associated with Behavioral Intention. This research contributes to the limited understanding of Mobile Healthcare Services in Indonesia and provides valuable insights into consumer behavior intention in the post-pandemic era.